2021
DOI: 10.3390/jcm10184281
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Subclinical Keratoconus Based on Machine Learning Techniques

Abstract: (1) Background: Keratoconus is a non-inflammatory corneal disease characterized by gradual thinning of the stroma, resulting in irreversible visual quality and quantity decline. Early detection of keratoconus and subsequent prevention of possible risks are crucial factors in its progression. Random forest is a machine learning technique for classification based on the construction of thousands of decision trees. The aim of this study was to use the random forest technique in the classification and prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Although topographic systems cannot measure the wavefront directly, they can estimate corneal aberrations from corneal steepening in ectatic areas that result in a deviation of rays projected onto the retina and a deformed wavefront [26] . In eyes with KC, the increase in anterior HOA, especially in coma, is caused by the irregular steepening and protrusion of the anterior corneal surface, which can be detected with high reliability by camera-based Scheimpflug topography systems [27] . However, even with RGP lenses, residual HOAs remain on the eye, typically attributed to the posterior corneal surface [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Although topographic systems cannot measure the wavefront directly, they can estimate corneal aberrations from corneal steepening in ectatic areas that result in a deviation of rays projected onto the retina and a deformed wavefront [26] . In eyes with KC, the increase in anterior HOA, especially in coma, is caused by the irregular steepening and protrusion of the anterior corneal surface, which can be detected with high reliability by camera-based Scheimpflug topography systems [27] . However, even with RGP lenses, residual HOAs remain on the eye, typically attributed to the posterior corneal surface [7] .…”
Section: Discussionmentioning
confidence: 99%
“…In their study of 61 healthy eyes and 20 eyes with subclinical keratoconus, Castro-Luna et al classified subclinical keratoconus using the random forest model with 89% accuracy, 93% specificity, and 86% sensitivity. 15 The progression of subclinical cases to clinically observable keratoconus suggests that subclinical cases have a similar but milder corneal disorder to those with keratoconus. For this reason, it would not be wrong to say that subclinical cases in the four map have changes similar to those of keratoconus, but cannot be distinguished by the human eye.…”
Section: Discussionmentioning
confidence: 99%
“…13 In recent years, deep learning-based studies that support the clinician's decision in the detection of keratoconus disease have attracted attention. [14][15][16] Kuo et al used three different convolutional neural network (CNN) models for keratoconus screening based on corneal topographic images. Sensitivity and specificity were determined at 0.90 levels with these models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have compared machine learning algorithms to detect ffKCN. Castro-Luna et al [38] found that the random forest outperformed decision tree model (89% accuracy vs. 71%, respectively) based on tomographic and biomechanical variables. Cao et al [39] also found the random forest model outperformed other machine learning algorithms using tomographic and demographic data, while Aatila et al [40] found the random forest model to have the highest accuracy compared to other machine learning models trained on anterior segment (AS)-OCT images in detecting all classes of KCN including ffKCN.…”
Section: Methodsmentioning
confidence: 99%